ON THE CALCULATION OF SECTIONS REINFORCED BY REPAIR COMPOUNDS - A. V. Kolleganov; N. A. Kolleganov; D. R. Mailyan; G. V. Nesvetaev (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the study isto assess the influence of concrete deformation properties during the restoration and (or)  reinforcement of reinforced-concrete sections using repair compounds.Methods. In the study, a method of calculation of the load-carrying capacity of concrete sections is used according to a non-linear  deformation model using diagrams of concrete deformation, taking  into account the influence of the confinement effect and prescription  factors on the deformation properties of concrete. Deformation  diagrams are constructed for short-term loading of concrete of various classes, taking into account the possible change in its  deformation properties due to its structural features (e.g. fine- grained) and the presence of modifying additives (repair concrete) in its the composition.Results. The increase in the load-bearing capacity of a section with its total area unchanged is not directly proportional to the area of  the reinforced concrete. The increase in the loadbearing capacity of  the section is not directly proportional to the increase in the class of  concrete reinforcement. Increasing the confinement coefficient from  1.3 to 1.5 provides an increase in the loadbearing capacity of the section from 15.5% to 58%. An increase in the elastic modulus of repair concrete by 1.5 times leads to an increase in the load-bearing  capacity of the section from 19% to 50%. While keeping sectional  value and reinforcement factor constant, the use of repair concrete  makes it possible to increase the bearing capacity of the section under consideration from 1.07 to 2.25.Conclusion. The calculation of the strength of reinforced concrete  elements reinforced with repair compounds according to the  nonlinear deformation model allows the stress-strain state (SSS) –  and, consequently, the bearing capacity after the reinforcement – to  be estimated more accurately, while the choice of the repair  compound depends on the deformation properties of the “old”  concrete.